Early anthropic occupation and geomorphological changes in South America: human–environment interactions and OSL data from the Rincão I site, southeastern Brazil - Cheliz, Pedro Michelutti; Giannini, Paulo Cesar Fonseca; Moreno de Sousa, João Carlos; Ladeira, Francisco Sergio Bernardes; Rodrigues, Juliana Alves; Mingatos, Gabriela Sartori; Pupim, Fabiano Nascimento; Mineli, Thays Desiree; Galhardo, Danilo [UNESP]; Rodrigues, Robson Antonio (My University, 2023)
This article aims to refine the description of the artefacts and the geomorphological, geological, pedological and chronological (optically stimulated luminescence (OSL) analyses of sedimentary deposits) characterisation of the Rincão I site (southeastern Brazil) to contribute to the understanding of early human–environment interactions. The archaeological site occupation took place on hillslopes truncated by the Mogi-Guaçu River's lateral (~1200 m) and vertical (~5 m) movements during the Late Quaternary, in an area where in situ bedrock outcrops are uncommon. This geological context favoured human groups simultaneously having access to the resources provided by the alluvial plain and hillslopes. Here we describe how about three hundred lithic artefacts are associated with soils that originated from sandy colluvium with OSL ages between 20.3 and 5.5 thousand years. These ages are consistent with the local palaeopedological and geomorphological contexts of landscape changes, and partly controversial from the perspective of models currently in vogue for the human occupation of southeastern Brazil. The vestiges of past human presence amid the hillslope sandy colluvium deposits include: 1) a set of flakes and formal artefacts (one stemmed point and three convex artefacts) made of sandstone obtained from hillslopes near (<10 km) the site; and 2) predominant detritus and flakes of quartz and flint obtained mostly from the adjacent (<1.5 km) alluvial plain, linked to flaking sequences other than those of the formal artefacts. Only quartz artefacts were found in the lower levels of the site stratigraphy, whereas in the intermediate and upper levels quartz, flint and sandstone artefacts were found, suggesting that there were changes in the raw materials used for flaking over time. The formal artefacts from the site have technological attributes like the ones observed in assemblages associated with a previously known lithic industry (Rioclarense), but a different pattern of choice of raw materials. This suggests that technical standards underwent a process of adaptation to the environmental particularities surrounding the Rincão I site.
Keywords: alluvial plain occupation; geoarchaeology; hillslope occupation; Late Quaternary; palaeopedology